Comparison of multibubble and single-bubble sonoluminescence spectra - Matula, TJ; Roy, RA; Mourad, PD; McNamara, WB; Suslick, KS (American Physical Society, 1995)
Comparisons of the spectral characteristics of sonoluminescence from cavitation in bubble fields (MBSL) versus cavitation of single bubbles (SBSL) have been made for aqueous solutions under similar experimental conditions. In particular, alkali metal chloride solutions exhibit sonoluminescence emission from excited state Na or K atoms in MBSL, while SBSL exhibits no such emission. Since the metal ions are not volatile, participation of the initially liquid phase must occur in MBSL. Surface wave and microjet formation in cavitating bubble fields versus the high spherical symmetry of collapse of an isolated bubble may account for the observed differences.